Helicobacter pylori infection in children with celiac disease: Multi-center, cross-sectional study - ERTEM ŞAHİNOĞLU, DENİZ; TUTAR, ENGİN (WILEY, 2020)
Background An inverse association has been suggested between celiac disease (CD) and Helicobacter pylori (Hp) infection in children; however, there are inconsistent data. The purpose of this multi-center study is to evaluate the association between Hp and CD in childhood. Methods Children who underwent endoscopy between July 2016 and November 2017 in four pediatric gastroenterology centers were included in the study. Patients with a history of previous Hp eradication, antibiotic or acid-suppressive drug therapy in the last 4 weeks, and any underlying chronic disease were excluded. The presence of Hp infection was confirmed by both histopathology and the rapid urease test. The ones who had the diagnosis of CD were compared with the children who underwent endoscopy during the same period and had another diagnosis. Duodenal histopathology of children with CD was categorized according to the modified Marsh classification. Results Of 3056 endoscopies performed in the study period, 2484 cases were eligible for the study. A total of 482 CD patients (mean age: 9.71 +/- 4.63 years, 58.5% girls) and 2060 controls (mean age: 9.92 +/- 4.66 years, 54.6% girls) were included in the study. The rate of Hp infection was significantly lower in CD group (26.3% vs 50.1%, P < .01). The difference was prominent even in children younger than 6 years old (P < .01). There was no correlation between Hp infection and the modified Marsh scores in CD (P > .05). Conclusion In this cross-sectional study, where Hp infection is common even in the pediatric population, the frequency of Hp infection was significantly lower in children with CD compared with the controls. Systematic cohort studies are necessary to clarify causal association between Hp infection and the development of celiac disease.
Keywords: celiac disease; children; Helicobacter pylori; modified Marsh classification; DUODENAL INTRAEPITHELIAL LYMPHOCYTOSIS; PREVALENCE; RISK; GUIDELINES; DIAGNOSIS; SOCIETY